About the diskrete Fourier transform calculation with the use of quasi-fundamehtal exponential functions - Денисюк, В. П.; Рибачук, Л. В. (Problems of Informatization and Control, 2009)
The discrete Fourier transform with the use of quazi-fundamental interpolating functions of exponential type is considered. It is shown that calculations of the discrete Fourier transform with these functions applying allow to obtain quickly decreasing estimations of the Fourier transform significances